AB0464 Lipid Changes Produced by Tocilizumab in the Treatment of Patients with Rheumatoid Arthritis in Santo Domingo, Dominican Republic. (9th June 2015) - Paula, J.; Ismely, P.; Susana, A.; Jeanette, M.; Roberto, M.; Violeta, R.; Valdez, T.; Feriz, A.
Abstract : Background: Rheumatoid Arthritis (RA) is a systemic, inflammatory, chronic, autoimmune disease that predominantly affects the joints. 1 In the last decade new drugs have been introduced, including biological drugs that act on different targets implicated in the pathogenesis of the disease. 2 Within this group of drugs is tocilizumab, a humanized monoclonal antibody anti IL-6r, key cytokine involved in the pathogenesis of RA and the disease activity. 3 Tocilizumab use has been associated with abnormal lipid profile consisting of an increase in total cholesterol, LDL cholesterol, HDL cholesterol, triglycerides and apolipoprotein A1 and B1. 4 Objectives: To determine the frequency of lipid abnormalities in patients with RA treated with tocilizumab in Santo Domingo, Dominican Republic. Methods: We performed an analytical, longitudinal, observational, prospective study. The records of patients diagnosed with RA who fulfilled the 1987 ACR criteria and ACR/EULAR 2010, which use biological therapy with Tocilizumab in HDPB and HFMP in July 2013 until August 2014 were reviewed. All patients signed informed consent and the study was approved by the ethics committee concerned. We reviewed a total of 56 records from which we selected patients who had at least 2 follow-up visits after the start of treatment (31 patients) taking into account the baseline lipid values to compare changes. The patients whose records were found incomplete during the first 3 visits were excluded. The frequency of continuous variables was analyzed using the SPSS statistical program (V20.x86). Results: Of 31 patients, 90.3% (28) corresponds to the female with a mean age of 52.5. 35.5% (11) had elevated total cholesterol, 12% (4) of LDLc, 25% (8) HDLc; 35.5% (11) presented elevated triglycerides and 12.9% (4) had together total cholesterol and triglycerides elevation. In the first visit, 48% of patients had increased levels of total cholesterol between 201-251 mg /dl and the third visit this increased to 51.6%. Similar changes were observed in relation to the levels of triglycerides, which at first visit was observed 13.3%, compared with 29% and 16% for the second and third visits respectively. Different results were observed with HDL levels because only significant alteration of this was observed, on the second visit, with 51.6%, compared to 30% in the 1st and 3rd visit. Conclusions: The monitoring of lipid levels in our study demonstrated that treatment with Tocilizumab was associated with increased lipid levels with no clinical significance, as described in the literature. We need to make long-term effect studies of this drug to be used as reference in conducting further studies and management protocols. References: Ann Rheum Dis 2014, 73:1607-1615. Lancet 2008;371:987–97. Ann Rheum Dis. 2008;67:516–23. Reumatol Clin. 2011;6(S3):S29–S32. Disclosure of Interest: None declared